Microenvironment of saphenous vein graft preservation prior to coronary artery bypass grafting. (6th July 2018) - Chen, Shao-Wei; Chu, Yen; Wu, Victor Chien-Chia; Tsai, Feng-Chun; Nan, Yu-Yun; Lee, Hsin-Fu; Chang, Chih-Hsiang; Chu, Pao-Hsien; Wu, Semon; Lin, Pyng-Jing
Abstract: OBJECTIVES: The best preservation solution for a free vascular graft prior to coronary artery bypass grafting (CABG) remains controversial. The aim of this investigation was to evaluate the microenvironment of the human saphenous vein graft when preserved in normal saline (NS) solution or autologous heparinized whole blood (AWB). METHODS: Between January 2014 and December 2014, 21 patients who underwent CABG were enrolled and a total of 162 saphenous vein graft rings were collected. NS and AWB were used to investigate the influence of the microenvironment. The hypoxia, oxidative stress and vascular apoptosis were assayed by western blot, and endothelial integrity was assessed by immunohistochemical analysis. RESULTS: The level of PaO2 in AWB was lower than that in NS (median: 100.5 mmHg vs 185.8 mmHg, P  =   0.004). This hypoxic condition led to the production of more hypoxia-inducible factor-1 (median: 60.1% vs 15.1%, P  =   0.008) and endothelial nitric oxide synthase (median: 52.6% vs 25%, P  =   0.046) within 30 min of preservation time. The fact that higher levels of glutathione peroxidase resulted in the preservation of AWB suggests that it is beneficial to boost the vascular antioxidant defense with lower levels of NOX2. AWB led to increased Bcl-2, reduced cytochrome c and cleaved 85 kDa poly ADP-ribose polymerase apoptotic fragments. CONCLUSIONS: We concluded that AWB possesses a microenvironment that is superior to that of NS for saphenous vein graft preservation prior to CABG.